Understanding food : principles and preparation - Brown, Amy C. (Australia : Thomson Wadsworth, 2005)
This book brings together the most current information in food science, nutritions, and food service to provide a comprehensive resource for students. [The text] represents information related to the science of food, including food selection and evaluation, food chemistry, and food safety. [It] covers aspects of food service, from meal planning and equipment to the basics of food preparation, food preservation, and government regulation of foods. [It] cover[s] all of the standard food items, include sweeteners, fats and oils, dairy products, meats, vegetables and fruits, soups and salads, grains, and breads, as well as desserts and beverages. [It also covers] culinary techniques, low-fat preparation methods, and the latest methods for food preservation and food safety.
Food science and nutrition -- Food service -- Food items -- Desserts and beverages.
Includes index.
Keywords: FOOD